Niosomal Gel of Lornoxicam for Topical Delivery: In vitro Assessment and Pharmacodynamic Activity - Kumbhar, Deepak (Springer US, 2013)
Lornoxicam is a potent oxicam class of non steroidal anti-inflammatory agent, prescribed for mild to moderate pain and inflammation. Niosomal gel of lornoxicam was developed for topical application. Lornoxicam niosomes (Lor-Nio) were fabricated by thin film hydration technique. Bilayer composition of niosomal vesicles was optimized. Lor-Nio dispersion was characterized by DSC, XRD, and FT-IR. Morphological evaluation was performed by scanning electron microscopy (SEM). Lor-Nio dispersion was incorporated into a gel using 2% w/w Carbopol 980 NF. Rheological and texture properties of Lor-Nio gel formulation showed suitability of the gel for topical application. The developed formulation was evaluated for in vitro skin permeation and skin deposition studies, occlusivity test and skin irritation studies. Pharmacodynamic activity of the Lor-Nio gel was performed by carragenan-induced rat paw model. Optimized Lor-Nio comprised of Span 60 and cholesterol in a molar ratio of 3:1 with 30 μM dicetyl palmitate as a stabilizer. It had particle size of 1.125 ± 0.212 μm (d(90)), with entrapment efficiency of 52.38 ± 2.1%. DSC, XRD, and IR studies showed inclusion of Lor into niosomal vesicles. SEM studies showed spherical closed vesicular structure with particles in nanometer range. The in vitro skin permeation studies showed significant improvement in skin permeation and skin deposition for Lor-Nio gel (31.41 ± 2.24 μg/cm(2), 30.079 ± 1.2 μg/cm(2)) over plain lornoxicam gel (7.37 ± 1.27 μg/cm(2), 6.6 ± 2.52 μg/cm(2)). The Lor-Nio gel formulation showed enhanced anti-inflammatory activity by exhibiting mean edema inhibition (87.69 ± 1.43%) which was significantly more than the plain lornoxicam gel (53.84 ± 2.21%).